No Correlation Between Plantar Flexor Muscle Volume and Sprint Performance in Sprinters - Miyake, Yuto; Suga, Tadashi; Terada, Masafumi; Tanaka, Takahiro; Ueno, Hiromasa; Kusagawa, Yuki; Otsuka, Mitsuo; Nagano, Akinori; Isaka, Tadao (Frontiers in Sports and Active Living, 2021)
The plantar flexor torque plays an important role in achieving superior sprint performance in sprinters. Because of the close relationship between joint torque and muscle size, a simple assumption can be made that greater plantar flexor muscles (i.e., triceps surae muscles) are related to better sprint performance. However, previous studies have reported the absence of these relationships. Furthermore, to examine these relationships, only a few studies have calculated the muscle volume (MV) of the plantar flexors. In this study, we hypothesized that the plantar flexor MVs may not be important morphological factors for sprint performance. To test our hypothesis, we examined the relationships between plantar flexor MVs and sprint performance in sprinters. Fifty-two male sprinters and 26 body size-matched male non-sprinters participated in this study. On the basis of the personal best 100-m sprint times [range, 10.21 to 11.90 (mean ± standard deviation, 11.13 ± 0.42) s] in sprinters, a K-means cluster analysis was applied to divide them into four sprint performance level groups (n = 8, 8, 19, and 17 for each group), which was the optimal number of clusters determined by the silhouette coefficient. The MVs of the gastrocnemius lateralis, gastrocnemius medialis, and soleus in participants were measured using magnetic resonance imaging. In addition to absolute MVs, the relative MVs normalized to body mass were used for the analyses. The absolute and relative MVs of the total and individual plantar flexors were significantly greater in sprinters than in non-sprinters (all P < 0.01, d = 0.64 to 1.39). In contrast, all the plantar flexor MV variables did not differ significantly among the four groups of sprinters (all P > 0.05, η2 = 0.02 to 0.07). Furthermore, all plantar flexor MV variables did not correlate significantly with personal best 100-m sprint time in sprinters (r = －0.253 to 0.002, all P > 0.05). These findings suggest that although the plantar flexor muscles are specifically developed in sprinters compared to untrained non-sprinters, the greater plantar flexor MVs in the sprinters may not be important morphological factors for their sprint performance.